2022
DOI: 10.3390/e24121721
|View full text |Cite
|
Sign up to set email alerts
|

Fisher Information Perspective of Pauli’s Electron

Abstract: An electron moving at velocities much lower that the speed of light with a spin, is described by a wave function which is a solution of Pauli’s equation. It has been demonstrated that this system can be viewed as a vortical fluid which has remarkable similarities but also differences with classical ideal flows. In this respect, it was shown that the internal energy of the Pauli fluid can be interpreted, to some degree, as Fisher Information. In previous work on this subject, electromagnetic fields which are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…T α0 denotes the temperature of the "fluid element" in the rest frame, and P α0 is the pressure of the same. The rest of the thermodynamic analysis follows the same analysis in equation A29-A34 of [1] in which attention should be paid to the fact that it is only correct in the rest frame.…”
Section: Variational Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…T α0 denotes the temperature of the "fluid element" in the rest frame, and P α0 is the pressure of the same. The rest of the thermodynamic analysis follows the same analysis in equation A29-A34 of [1] in which attention should be paid to the fact that it is only correct in the rest frame.…”
Section: Variational Analysismentioning
confidence: 99%
“…The variation of internal energy is the only new calculation with respect to the calculation done for a system of particles described previously [8], thus the rest of the analysis is trivial. Varying equation (1) we thus obtain:…”
Section: Variational Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…It was also suggested that one may define comoving scalar fields as in ideal fluid mechanics, however, this was only demonstrated implicitly but not explicitly. A common feature of previous work on the fluid & Fisher information interpretation of quantum mechanics, is the negligence of electromagnetic interaction thus setting the vector potential to zero, this was recently corrected in [30].…”
Section: Introductionmentioning
confidence: 99%